An innovative approach combining Animal Performances, nutritional value and sensory quality of meat. (December 2016) - Ellies-Oury, M.-P.; Cantalapiedra-Hijar, G.; Durand, D.; Gruffat, D.; Listrat, A.; Micol, D.; Ortigues-Marty, I.; Hocquette, J.-F.; Chavent, M.; Saracco, J.; Picard, B.
Abstract: This work sets out a methodological approach to assess how to simultaneously control together Animal Performances, nutritional value, sensory quality of meat. Seventy-one young bulls were characterized by 97 variables. Variables of each element were arranged into either 5 homogeneous Intermediate Scores (IS) or 2 Global Indices (GI) via a clustering of variables and analysed together by Principal Component Analysis (PCA). These 3 pools of 5 IS (or 2 GI) were analysed together by PCA to established the links existing among the triptych. Classification on IS showed no opposition between Animal Performances and nutritional value of meat, as it seemed possible to identify animals with a high butcher value and intramuscular fat relatively rich in polyunsaturated fatty acids. Concerning GI, the classification indicated that Animal Performances were negatively correlated with sensory quality. This method appeared to be a useful contribution to the management of animal breeding for an optimal trade-off between the three elements of the triptych. Highlights: This work concerns animal performances, nutritional value and sensory quality. An innovative methodological approach to combine these three elements is proposed. There is no opposition between animal performances and nutritional value of meat. Animal performances appear negatively correlated with sensory quality. This method is a useful contribution to the management of animal breeding.